2022
DOI: 10.3390/app12126195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Steam Autoclaving on the Mechanical Properties of 3D-Printed Resins Used for Insertion Guides in Orthodontics and Implant Dentistry

Abstract: Guided implant placement has been shown to be more accurate than free-handed insertion. Still, implant position deviations occur and could possibly pose risks. Thus, there is a quest to identify factors that might impair the accuracy of implantation protocols using templates. This study aimed to investigate the influence of autoclaving cycles (cycle 1: 121 °C, 1 bar, 20.5 min; cycle 2: 134 °C, 2 bar, 5.5 min) on the Vickers hardness and flexural modulus of five different materials used for 3D-printed insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previous research has shown that the mechanical properties of 3D printed samples made of the same materials used in the present study were altered when cycle 2 was used, leading to a decrease in flexural modulus in one material, while no such changes occurred for cycle 1 (Kirschner et al, 2022). Both the curing layer thickness and the angulation of the guide during the printing process have been shown to impact the intaglio surface of the surgical guide (Dalal et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…Previous research has shown that the mechanical properties of 3D printed samples made of the same materials used in the present study were altered when cycle 2 was used, leading to a decrease in flexural modulus in one material, while no such changes occurred for cycle 1 (Kirschner et al, 2022). Both the curing layer thickness and the angulation of the guide during the printing process have been shown to impact the intaglio surface of the surgical guide (Dalal et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…Regarding other factors that influence template accuracy, Zhou et al (Zhou et al, 2018) conducted a comprehensive comparison of various clinical factors and concluded that guide accuracy may be affected by guide position (maxilla or mandible), guide fixation (fixation screw or not) (Pessoa et al, 2022), type of guide (total or partial) (Mangano et al, 2018;Lou et al, 2021;Fotopoulos et al, 2022;Gargallo-Albiol et al, 2022), flap approach (open flap or flapless), differences in implant system (Zhu et al, 2021), high temperature sterilization (Marei et al, 2019;Kirschner et al, 2022) and support mode (tooth-supported, mucosa-supported or mixed-supported) (Pan et al, 2022). In addition, Henprasert et al concluded that there was no significant difference in accuracy between 3D-printed and milled guides, but found that the former had the advantages of high efficiency and reduced material waste (Henprasert et al, 2020).…”
Section: Research Status On Additive Manufacturing Applications In Im...mentioning
confidence: 99%
“…Te autoclave is a special pressure device consisting of an autoclave body, autoclave body fange, autoclave cover, autoclave cover fange, swing device, and safety device. It is also widely used in industries requiring high-temperature and high-pressure processing, such as metal smelting, chemical fber production, heating concrete pipe piles, gray sand bricks, microporous calcium carbonate, and asbestos slabs [1][2][3][4][5][6][7]. In order to quickly implement repeated operations such as rotation, boosting, steaming, depressurization, and unwinding during material loading and unloading, autoclaves generally have a pass-through or snap-on fast-opening structure.…”
Section: Introductionmentioning
confidence: 99%